Systematization of an Experience: Transformation of the Academic Practices of the Course Introduction to Business, Guápiles Campus, University of Costa Rica, in the Context of COVID-19 - Arguedas Ulloa, Ariel Jesús (2023)
Description: This paper describes the good academic practices adopted after the global health crisis that has affected the educational field. Objective: To describe the steps to achieve transformation in the academic practices of the Introduction to Business Administration course University of Costa Rica. Methodology: The five-time methodology recommended by Jara (2011) has been used. Results: The great transformation in academic practices lies in the fact that the methodology becomes 100% virtual, where the teacher had to previously design the teaching material for his synchronous class and add asynchronous educational elements that make him approach the subject, objectives, and share them through a pedagogical strategy with students, while relying on non-traditional digital tools. Conclusions: The global context forces all teachers to modernize the structure of physical or virtual classrooms depending on the student with dynamic and interactive spaces; in addition, it is concluded that academic practices are not an occurrence. Rather, it is a planned process in which evaluation and accompaniment with peers is of great help for instructional design.